Development of urea biosensor using non-covalent complexes of urease with aldehyde derivative of PEG and analysis on serum samples - Vardar, Gokay; Attar, Azade; Yapaoz, Melda Altikatoglu (TAYLOR & FRANCIS INC, 2019)
Non-covalent complexes of urease/polyethylene glycol (PEG)-aldehyde were synthesized using regular molar ratios of urease and PEG-aldehyde at room temperature. The physical properties of the non-covalent complexes were analyzed in order to investigate the impact of coupling ratio, temperature, pH, storage stability, and thermal stability. Urease activity was analyzed by UV-Vis spectrophotometer at 630 nm. The results showed that the strongest thermal resistance was obtained using n(U)/n(PEG):1/1 (mg/mL) complex within all molar ratios tested. The enzymatic activity of n(U)/n(PEG):1/1 complex doubled the activity of the free enzyme. Therefore, this complex was chosen to be used in the analyses. When coupled with PEG-aldehyde, urease exhibited improved activity between pH 4.0-9.0 and the optimum pH was found to be 7.0. The thermal inactivation results of the complex demonstrated that higher activity remained (40%) when compared with the free enzyme (10%) at 60 degrees C. The storage stability of the non-covalent complex was 4 weeks which was greater than the storage stability of the free enzyme. A kinetic model was suggested in order to reveal the mechanism of enzymatic conversion. Potentiometric urea biosensor was prepared using two different membranes: carboxylated poly vinyl chloride (PVC) and palmitic acid containing PVC. The potentiometric responses of both sensors were tested against pH and temperature and the best results were obtained at pH 7.0 and 20-30 degrees C. Also, selectivity of the suggested biosensors toward Na+, Li+ Ca2+, and K+ ions was evaluated and the reproducibility responses of the urea biosensors were measured with acceptable results.
Keywords: Enzyme-polymer modifications; non-covalent complexes; PEG-aldehyde; urea biosensor; urease; IMMOBILIZATION; ENCAPSULATION; STABILITY; DEXTRAN; ENZYMES; FIBERS; ALADH; Biochemistry & Molecular Biology; Biotechnology & Applied Microbiology